A New Ultra High-Performance Liquid Chromatography-Tandem Mass Spectrometry Method to Monitor 1-Amino-4-Methyl-Piperazine and 1-Methyl-4-Nitroso-Piperazine in Rifampicin Hydrolysis: A Standard Addition Approach to Quantify Nitrosamine in Rifampicin - Alessia Panusa; Paola Rotundo; Daniele Sadutto; Andrea Rodomonte; Roberto Cirilli (Separations, 2024)
1-amino-4-methyl-piperazine (AMP) is both a starting material for the synthesis of rifampicin (RIF) and a degradation product of RIF hydrolysis. 1-methyl-4-nitroso-piperazine (MNP) is an oxidation product of AMP as well as a potentially genotoxic N-nitrosamine. The EMA and FDA have approved an ad interim limit of 5 ppm for MNP in RIF drug products. As in-house methods for the analysis of MNP in RIF use a wide range of conditions for mobile phases and sample diluents, we decided to investigate whether these conditions affect the formation of MNP and AMP. A UHPLC-MS/MS method was developed to simultaneously quantify AMP and MNP during RIF hydrolysis in buffered aqueous solutions at different pH levels. Analyses were performed in MRM mode; separations were carried out on an InfinityLab Poroshell HPH-C18 (100 mm, 2.1 mm i.d., particle size 1.9 μm). In aqueous RIF solutions, the content of AMP and MNP increases with time; at different pHs, the concentration of AMP increases much faster in acidic than in basic solutions; and the increase in MNP can be reduced by the addition of ascorbic acid. To avoid an overestimation of MNP, water should not be used as a diluent in RIF sample preparations. Methanol is a more suitable diluent than water. A standard addition method has been validated for the quantification of MNP in RIF drug substances.